A measurement-to-modelling approach to understand catchment-to-reef processes: sediment transport in a highly turbid estuary - Xiao, Ziyu; Carlin, Geoffrey; Steven, Andrew D. L.; Livsey, Daniel N.; Song, Dehai; Crosswell, Joseph R. (Frontiers in Marine Science, 2023)
As sediments carried by rivers enter coastal waters, fine particles can reduce the amount of light that reaches the reef through light attenuation. The Fitzroy Estuary -Keppel Bay (FE-KB), being the second-largest source of sediments to the Great Barrier Reef (GBR) poses a significant threat to the GBR ecosystem such as coral reefs and seagrass meadows, and biogeochemical cycles that influence water clarity. While monitoring and modelling capabilities for catchment and marine settings are now well-developed and operational, a remaining key gap is to better understand and model the transport, dynamics and fate of catchment derived material through tidally influenced sections of rivers that discharge into the GBR. This study aims to reveal sediment transport in the FE-KB estuary by continuously monitoring the seasonal variability over a year-long period and build a high-resolution model to predict sediment budgets under different scenarios of physical forcing and river conditions.Multiple data sources, including field surveys, historical data, and numerical modelling were used to obtain a detailed understanding of the sediment transport processes during wet (high river flow) and dry (low-to-no river flow) seasons. The use of high-resolution bathymetry and survey data for sediment model parameterization allowed for accurate mapping of the morphological changes, while numerical modeling provided insights into the hydrodynamic and sediment transport processes in the estuary. Observation and model data confirm the existence of a Turbidity Maximum Zone (TMZ) in the FE-KB (approximately 35 -40 km from estuary head), where the topography plays a critical role in trapping sediments. By utilizing the model, a closed sediment budget was calculated under varying flow conditions and the results were used to determine the estuarine trapping coefficient that ranges from 28% (during extreme wet condition) to 100% (during dry condition) of the total catchment loads. Morphodynamic modelling demonstrated a persistent erosion pattern in the upper reach of the FE. The lower FE and southern tidal creeks serve as a large sediment storage basin during both wet and dry seasons, and sediment is exported and deposited offshore during high river flow conditions.